Diagnostic Evaluation of Patients Presenting with Rectal Bleeding by Colonoscopy - Malla, Bala R; Simkhada, Suyog (Journal of Institute of Medicine Nepal, 2020)
Introduction Rectal bleeding indicates the bleeding from lower gastro-intestinal tract occurring distal to ligaments of Treitz. Annual incidence of per rectal bleeding has been estimated to be 20% . Colonoscopy is the examination of choice for investigation. The objective of this study is to know the diagnostic yield of colonoscopy in cases with per rectal bleeding and to know the common causes of per rectal bleeding in adults Methods One hundred and twenty-nine adult patients, age more than 18years, who presented to Surgical OPD and ward of Dhulikhel Hospital during the year 2018 and 2019 were taken for the study irrespective of their sex. All the patients were subjected to fibre-optic colonoscopy after necessary preparation and the findings were recorded. Diagnosis was based on colonoscopic and histopathologic findings. Results A total of 129 (77 male and 52 female )patients with per rectal bleeding were evaluated with colonoscopy. The age ranged from 18 years to 79 years with the mean age 42.25 (SD+/- 15.29). Colonoscopy showed abnormalities in 102 patients (79.06%). The most common finding was hemorrhoids in 36 patients (27.90%) followed by colorectal malignant mass in 20 patients (15.50%). Polyps were diagnosed as the cause of rectal bleeding in 14 patients (10.84%). Conclusion Colonoscopy has good diagnostic yield at evaluating cases with per rectal bleeding. Hemorrhoids, colorectal malignant mass and polyps are the common causes producing PR bleeding in Nepalese adult population.